PENGARUH POTENSI SEKTOR KEMARITIMAN DAN PERTUMBUHAN TENAGA KERJA PADA SUBSEKTOR KEMARITIMAN BAGI PENINGKATAN PEREKONOMIAN DAERAH DI KABUPATEN CILACAP - Kristian Cahyandi (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2017)
Orientation of regional development, especially coastal areas it is time to make marine sector as one of development priorities. Coastal areas should consider and make marine potential as one of the doors of economic development, so that it can be aligned and relevant to the current demands of national development based on marine resources. From a social and cultural perspective, marine-based development is also a reinventing aspect of life that was once dominant in the culture and traditions of the Indonesian nation.The achievement of development results in the marine-based sector provides a diverse picture. From the subsector that can be classified as business fields in the marine sector such as fisheries, marine tourism, mining and energy, maritime industry, sea transportation, marine building and marine services, not all sectors give significant yield and contribution to the nation's economy.Cilacap regency located in the southern coast is very feasible for the development of maritime sector, with the support as the only district that has a port of goods on the south coast of Java.